Study on Polymorphism of Isfahan Native Chickens Population Using Microsatellite Markers - Nasiri, M.T. Beigi; Shokri, F.; Khanian, S. Esmaeil; Tavakoli, S. (International Journal of Poultry Science, 2007)
Polymorphism of Isfahan native chickens were evaluated using ten microsatellite markers. Nine microsatellite loci were found to be polymorphic, but one of them was monomorph (MCW0216). All microsatellite loci deviate from the Hardy-Weinberg equilibrium. Heterozygosity and the Polymorphism Information Content (PIC) were calculated to determine the genetic variation. Of the nine polymorphism loci, actual and effective number of alleles (na, ne) per locus ranged from 2 to 5 and 2 to 3.9014, respectively. PIC has values between 0.3750 to 0.6972 per locus (except monomorphic locus) and average of polymorphism information content based on 10 microsatellite was estimated as 0.4897 for this population. The average of heterozygosity exclusive of monomorphic locus ranged from 0.5 to 0.7437 per locus and by attention of monomorphic locus was 0.5613 per population. In general, it can be concluded that Isfahan native chickens population has approximately low genetic diversity. Therefore designing breeding project needs attention to conserving the genetic diversity, so the genetic resources will be conserved as world’s national investments.